FEM BASED 3-D SIMULATION AND HARDWARE DESIGN OF POWER AMPLIFIER FOR SINGLE COIL ACTIVE MAGNETIC BEARING - LALDINGLIANA, JONATHAN; KUMAR BISWAS, PABITRA (International Journal of Psychosocial Rehabilitation, 2020)
Active magnetic bearing (AMB) is a bearing that levitates the rotor in the air without any physical contact between the actuator (an electromagnet) and the object (a rotor). For hovering the rotor of AMB in the air, it is important to supply the necessary measure of current through the coil. Therefore, proper selection of power amplifier for an AMB system is an absolute necessity. This paper deals with the 3-dimensional simulation of a single-coil AMB (SAMB) system using FEM-based software known as ANSYS Maxwell. Magnetic properties such as flux pattern, flux density, electromagnetic field, inductance, and force are obtained in this research work. Various sorts of power amplifiers are simulated in PSIM for the proposed SAMB system, and the most efficient amplifier is designed in hardware for validating the software result.